ICMS e guerra fiscal: a glosa unilateral de crédito de ICMS à luz da teoria geral do direito - Oliveira Júnior, José Galbio de (2023)
This research analyzes the disallowance of ICMS credits carried out unilaterally by state federated entities in view of the indication of unconstitutionality in the tax benefit in the state of origin, granted without prior authorization agreement. We seek to understand its framework in the general theory of law and its compatibility with the legal system, reviewing the scientific production on the subject